2017
DOI: 10.1590/1982-43272766201706
|View full text |Cite
|
Sign up to set email alerts
|

The Zulliger-CS in Elderly on Hemodialysis and the Relationship Between External Variables

Abstract: Abstract:The use of reliable instruments is an ethical condition to exert psychological evaluation. The aim of the study was to investigate the validity of the Zulliger test in the evaluation of elderly with chronic kidney disease (CKD) with focus on cognitive constructs and interpersonal relationships of elderly with Chronic Kidney Disease; and investigate the relationship with external variables. Palavras-chave: técnicas projetivas, avaliação psicológica, doenças crônicas, idosos El Zulliger-SC con Ancianos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
(28 reference statements)
0
4
0
6
Order By: Relevance
“…Some authors believe that PD patients voluntarily accept help and display less authoritarian and more passive behaviors because as the disease progresses, they tend to need more help and care (Bhimani, 2014;Queiroz, 2012). Surprisingly, Gregoleti and Scortegagna (2017) found reduced Fd in patients undergoing hemodialysis, however, they reported a positive relationship between family and social support. In addition to the underlying differences between CKD and the PD and the psychosocial characteristics of caregiving environments, the relationship between the external variables and a more active social and family support may have contributed to minimize dependent behaviors.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Some authors believe that PD patients voluntarily accept help and display less authoritarian and more passive behaviors because as the disease progresses, they tend to need more help and care (Bhimani, 2014;Queiroz, 2012). Surprisingly, Gregoleti and Scortegagna (2017) found reduced Fd in patients undergoing hemodialysis, however, they reported a positive relationship between family and social support. In addition to the underlying differences between CKD and the PD and the psychosocial characteristics of caregiving environments, the relationship between the external variables and a more active social and family support may have contributed to minimize dependent behaviors.…”
Section: Discussionmentioning
confidence: 79%
“…The available studies are related to the Brazilian normative data published in 2009 (Franco, Cardoso, Villemor-Amaral, & Primi, 2012) regarding the evidence for convergent and discriminant validity of the Pfister test (Franco & Villemor-Amaral, 2009) and the evaluation of older adults with Chronic Kidney Disease (CKD) (Gregoleti & Scortegagna, 2017). Investigating older people with CKD in a sample of 60 people, mean age of 73.1 years (Standard Deviation -SD = 5.8), Gregoleti and Scortegagna (2017), found that patients undergoing hemodialysis had interpersonal problems demonstrated by the decrease in the food responses (Fd) (p = 0.021, d = 0.65), isolation (p = 0.006, d = 0.61), and by the proportion of poor over good human representation responses (Poor Human Representations -PHR > Good Human Representations -GHR).…”
mentioning
confidence: 99%
“…The confrontation of stress and the control of negative emotions (Pinto et al, 2016), the social interaction and the academic performance (Bolsoni-Silva & Loureiro, 2014;Feitosa et al, 2012) are also reported in adults with higher social skills scores. In the study by Gregoleti and Scortegagna (2017), elderly patients with chronic kidney disease when compared to those free of disease, presented a decrease in R, which for the authors may derive from deprivation of leisure and interests, and employment restrictions.…”
Section: Del Prete and A Del Prete 2001)mentioning
confidence: 91%
“…número amostral variou de 1 a 100 participantes, a média de idade variou de 67,5 a 75 anos. Os estudos tiveram como objetivo avaliar o funcionamento psicológico e da personalidade dos idosos(GIL, 2001;OLIVEIRA et al, 2001;COELHO et al, 2010;DALLAGNOL, 2014); a validade e normatização dos instrumentos(BASTOS-FORMIGHIERI;PASIAN, 2012;GREGOLETI;RIEN et al, 2017) e entendimento do psicodiagnóstico (POZZI; BOFF, 2013). Estudos brasileiros com uso de testes projetivos na avaliação de idosos.…”
unclassified